SDRE-based high performance feedback control for nonlinear mechatronic systems. Issue 4 (24th June 2019) - Stepien, Slawomir Jan; Superczynska, Paulina; Dobrowolski, Damian; Dobrowolski, Jerzy
Abstract : Purpose: The purpose of the paper is to present modeling and control of a nonlinear mechatronic system. To solve the control problem, the modified state-dependent Riccati equation (SDRE) method is applied. The control problem is designed and analyzed using the nonlinear feedback gain strategy for the infinite time horizon problem. Design/methodology/approach: As a new contribution, this paper deals with state-dependent parametrization as an effective modeling of the mechatronic system and shows how to modify the classical form of the SDRE method to reduce computational effort during feedback gain computation. The numerical example compares described methods and confirms usefulness of the proposed technique. Findings: The proposed control technique can ensure optimal dynamic response, reducing computational effort during control law computation. The effectiveness of the proposed control strategy is verified via numerical simulation. Originality/value: The authors introduced an innovative approach to the well-known SDRE control methodology and settled their research in the newest literature coverage for this issue.